Corn Germ Color Detection during Storage in Kendal Regency, Central Java. Issue 1 (1st May 2022) - Al-Baarri, A N; Hadipernata, M; Legowo, A M; Abduh, S B M; Pratiwi, A F; Setyadi, B; Ranini, A A; Lestari, F P; Pangestika, W; Afra Mawarid, A; Somantri, M
Abstract: Kendal is in Central Java, Indonesia, and has large production in corn and prominent corn-produced-regency in Indonesia. Two varieties have been cultivated in this regency but no documentation on its appearance in germ color. This research was done to analyze the corn ness, yellowness, mushroom smell, and RH in the corn as a heating process to decrease water content in corn prior to its storage. The research used NK212 and Perkasa 72 corn varieties which were commonly obtained in this local area. The shininess, color appearance, and smell senses of the 25 panelists were used to detect shininess, yellowness, and mildew odor. The obtained data was explained using the relative humidity or RH value as supporting data. The automatic RH meter that was integrated and synchronized in the cloud was used to detect the RH of the corn seed. All samples were placed in the glass box with no additional treatment but was covered using thin cloth to avoid contamination and infection. The corn was stored for 6 months. As result, shininess, yellowness, mildew odor, and RH value provided specific value among these two varieties.